Pengaruh Media Video Tutorial Terhadap Kemampuan Menulis Teks Deskripsi Siswa Kelas VII Mtsn 2 Medan Tahun Pembelajaran 2023/2024 - Anzza Fellda Kasvita; Mara Untung Ritonga (Asosiasi Periset Bahasa Sastra Indonesia, 2024)
This research aims to determine the effect of video tutorial media on the ability to write descriptive text for students in class VII MTsN 2 Medan for the 2023/2024 academic year. The population of this study was all class VII MTsN 2 Medan for the 2023/2024 academic year, consisting of 10 classes with a total of 320 students. The samples taken were classes VII-1 and VII-4, totaling 32 students in each class. The method used is an experimental research method, this will use the